The impact of the combined lactoperoxidase and pasteurisation treatment on the safety of goat milk and cottage cheese - Buys, E.M. (Elna Maria) (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Food Production and Processing))--University of Pretoria, 2007.